PENGARUH PENERAPAN TINDAKAN PENGAMANAN PERDAGANGAN (SAFEGUARD) PRODUK IMPOR BENANG ASAL INDIA BAGI INDUSTRI TPT (TEKSTIL DAN PRODUK TEKSTIL) DI INDONESIA TAHUN 2011 - Fitri Rahmadani; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research discusses the Influence of Security measures product import cotton yarn from India for textile industry in indonesia 2011. This action is caused by the high volume of imports of cotton yarn products which resulted in the domestic cotton yarn industry suffered serious losses. In discussing the effect of the application of trade securing measures to the imported yarn of Indian cotton yarn for the Indonesian TPT industry in 2011, the authors used a qualitative research methodology, with the technique of library research to collecting data from book literature sources, magazine issues, Journals and various scientific articles. The perspective used is mercantilism. The level of analysis used is the Nation-State. The theory used is the theory of protectionism by Alexander Hamilton.The influence of the application of trade securing measures to Indian cotton yarn imported products for the Indonesian tpt industry in 2011 is the effect on the volume of cotton yarn imports which experienced the value of fluctuation which resulted in a domestic industry can not recover from the previous losses. Such conditions result in an application for extension of the application of trade securing measures and are granted through Regulation of the Minister of Finance Number. 96 / PMK.011 / 2014.Key words: Safeguard, protectionism, TPT industry